Comparative Study on the Hypocholesterolemic Activity of Amidated Polysaccharides and Psyllium - Milan Marounek (BioResources, 2015)
The effects of amidated carboxymethylcellulose, amidated pectin, and psyllium on serum and hepatic cholesterol, hepatic fat, and fecal output of sterols were examined in female rats. Rats were fed a diet supplemented with cholesterol (0 or 10 g/kg) and palm fat. Amidated cellulose at 30 g/kg significantly decreased the serum and hepatic concentration of cholesterol by 28.1% and 64.6%, respectively. Corresponding values in rats fed amidated pectin were 28.9% and 72.4%. The effects of psyllium were similar, but less pronounced. Amidated pectin significantly increased the fecal output of cholesterol, total neutral sterols, and total sterols by 49.1%, 31.9%, and 31.0%, respectively. Amidated cellulose and psyllium increased the fecal excretion of total sterols by 1.1% and 5.5%, respectively. In the feces of rats fed amidated cellulose, a small amount of conjugated bile acids was detected (0.83% of total bile acids). In these rats, the lowest expression of hepatic cholesterol 7α-hydroxylase was detected, corresponding to the low fecal output of bile acids. We conclude that the hypocholesterolemic effects of both amidated polysaccharides were similar in spite of their different affinity to sterols.